Estudo da eficiência de conversão de combustíveis de motor de ignição por centelha enriquecidos com mistura rica em hidrogênio obtida via reforma catalítica - Lucimar Venâncio Amaral (2024)
Fossil fuels account for 72% of the energetic demand in the transportation sector and 59% of carbon dioxide (CO2) emissions. In response to the need to supply the energetic demand and in line with the reduction of pollutants emissions, this work evaluates, through an experimental methodology and kinetic modeling, the effects of adding a gaseous synthetic mixture, which represents the concentration of a reforming gas with high-purity hydrogen experimentally got and validated from an ethanol vapor catalytic reforming process to two primary fuels (ethanol and gasoline). For comparison, high-purity hydrogen gas was also added to ethanol. The combustion kinetic modeling used the mass fraction burned (MFB) experimental data as an entrance parameter to analyze the combustion process. Ethanol and gasoline were inserted in the combustion chamber through direct injection (DI), and the gaseous synthetic mixture was added through the fumigation system (FS). The addition of high-purity hydrogen was also done through fumigation. The experimental methods were done in a research engine working within the main parameters from the FTP-75 standard cycle. The research engine was a four-times single-cylinder from AVL (model 5405). The ignition advances and the gaseous synthetic mixture percentage varied, with the intention of observing the behavior of the mixture air-fuel. Four rotations were used (1900, 2500, 3000, and 4500 rpm) combined with three indicated mean effective pressures (3.0, 5.0, and 8.0 bar) and full charge condition only for rotations at 3000 and 4500 rpm. Specifically, high-purity hydrogen addition to ethanol was done as an experimental procedure at only 2500 rpm and 3 bar. It were evaluated the indicated specific fuel consumption, the fuel conversion efficiency, exhaustion temperature, pollutants emissions (unburned hydrocarbons, CO, NOx, and CO2), and the evolution of the combustion process. The results showed that adding the synthetic gaseous mixture accelerated the combustion process when combined with the proposed primary fuels. The addition of the gaseous synthetic mixture to ethanol as primary fuel showed higher combustion acceleration when compared to gasoline, mainly at the points at 1900 rpm and 8.0 bar, and 2500 rpm with mean effective pressures of 3.0 and 5.0 bar. As a consequence of the process acceleration by using ethanol, a reduction in specific fuel consumption and better combustion centralization were observed, a fact that was not repeated when gasoline was used. It was observed that higher flows of the gaseous synthetic mixture are unnecessary for a significative specific consumption reduction, and it is safe when combined with ethanol. As the gaseous synthetic mixture can be obtained by loading it into the combustion engine, it is a viable alternative to the currently commercialized engines. The kinetic modeling analysis showed representative and comparable data to the experimental results, validating this method as a viable resource for analyzing the combustion process without the need to use experimental resources as the only methodological tool. Regarding the emissions, the results were not conclusive.